The Role of Internalized Stigma and Perceived Discrimination Regarding the Self-Esteem of People Living with HIV/AIDS in Jakarta - Yosef Dedy Pradipto; Bernadette N. Setiadi (ANIMA Indonesian Psychological Journal, 2019)
The aim of this study was to examine the role or internalized stigma and the perception of discrimination in relation to the self esteem of People Living with HIV/AIDS (PLWHA) in Jakarta, Indonesia. It would appear that negative stigmatization and discrimination towards PLWA in Indonesia have risen rapidly, in line with the increase in the number of people diagnosed with HIV/AIDS. The instruments employed were the Rosenberg Internalized Stigma, Perception of Discrimination, and Self Esteem scales. The participants in this study were PLWHA (N = 96), living in Jakarta, with an age range of 15 to 59 years. The results of regression analysis indicated that internalized stigma (t = 1.31; p > .05) and the perception of discrimination (t = - 0.50; p > .05) played no role in predicting self esteem amongst PLWHA. A difference is found regarding internalized stigma and perceived discrimination, seen from the viewpoint of the work status of the participants.